2019
DOI: 10.3906/tar-1805-62
|View full text |Cite
|
Sign up to set email alerts
|

Mesophyll protoplast isolation technique and flow cytometry analysis of ancient Platycladus orientalis (Cupressaceae)

Abstract: Platycladus orientalis (Cupressaceae) is a native tree species used widely for landscaping and afforestation in arid and semiarid areas in Asia. Ancient P. orientalis trees not only have an important humanistic and historical value but also have a significant scientific value in aging mechanism research. Mesophyll protoplasts are an important material for studies of plant regeneration, transient gene expression, and senescence. Although an easy and effective technique of mesophyll protoplast isolation from mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Platycladus orientalis (L.) Franco, belonging to the genus Platycladus (Cupressaceae) of evergreen coniferous tree species, is the main afforestation tree species in the arid regions of the Loess Plateau of Northwest China [4][5][6]. Due to its long lifespan, beautiful trunk, sacred status and important economic value, P. orientalis has been planted in gardens, temples and the vicinity of mausoleums since ancient times [7]. It is the most widely planted cemetery tree species in China [8].…”
Section: Introductionmentioning
confidence: 99%
“…Platycladus orientalis (L.) Franco, belonging to the genus Platycladus (Cupressaceae) of evergreen coniferous tree species, is the main afforestation tree species in the arid regions of the Loess Plateau of Northwest China [4][5][6]. Due to its long lifespan, beautiful trunk, sacred status and important economic value, P. orientalis has been planted in gardens, temples and the vicinity of mausoleums since ancient times [7]. It is the most widely planted cemetery tree species in China [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ratanasanobon and Seaton (2013) studied on protoplast isolation in Chamelaucium group plants with longer than 6 h of incubation time, protoplasts could not be released when treated with 2% cellulase and 1% macerozyme. Zhou et al (2019) reported that period of incubation significantly affects the yield and viability of protoplast in Platycladus orientalis, yield of viable protoplasts decreased after 16 h of incubation time. Different species have different requirements which influence the success of protoplast isolation.…”
Section: Discussionmentioning
confidence: 98%
“…The most favorable protoplast isolation efficiency was determined in the combination of 2% cellulase and 0.2% pectinase formulated protoplast digestion solution.The cellulase concentrations appeared to be crucial for callus protoplast isolation. Zhou et al (2019) reported that different cellulase and pectinase concentrations in the protoplast digestion solution remarkably affected protoplast yield. However, using cellulase at a concentration of 4% reduced the number of protoplasts isolated from the ovule-derived embryogenic callus of C. volkameriana in the present study.…”
Section: Discussionmentioning
confidence: 99%